Bacillus pumilus, a Novel Ginger Rhizome Rot Pathogen in China - Peng, Qin (Plant disease, 2013)
Ginger rhizome rot is a major factor limiting the yield and marketability of ginger in Shandong Province, China. In order to identify the pathogen causing ginger rhizome rot, evaluate its pathogenicity, and explore its pathogenesis, diseased ginger rhizomes and surrounding soils were collected. A gram-positive, spore-forming, rod-shaped bacterium, designated GR8, was frequently isolated from the ginger rhizome samples. The bacterium was identified as Bacillus pumilus based on physio-biochemical and molecular biology characteristics. Pathogenicity studies with GR8 showed that it could cause disease of the tested rhizomes slices and the entire rhizome when wounded but no disease occurred when the rhizome was not wounded. Preliminary pathogenicity studies demonstrated that cell-free cultures of GR8 could not cause any disease symptoms, whereas the bacterial suspensions caused severe symptoms. The pathology studies revealed that infection of GR8 could cause starch grains to shrink from normal size, and destroy the parenchyma cells by invading and propagating in them. This is the first report of B. pumilus causing ginger rhizome rot